Walisongo’s Concept of Religious Moderation in the History of Islamization of Java in the 15th Century AD - Wildhan Ichza Maulana (Tamaddun, 2022)
This research offers a review of the concept of Walisongo's religious moderation. As for mapping the concept of religious moderation in Walisongo comprehensively, four indicators of moderation of the Ministry of Religion of the Republic of Indonesia are used as an analytical tool, including national commitment, tolerance, anti-violence, and accommodativeness to local culture. This research is descriptive qualitative research using the historical method. Meanwhile, primary data sources were obtained from the book "Atlas Walisongo", and secondary data sources were obtained from several other supporting kinds of literature. The results of this study show that Walisongo's concept of moderation in terms of four indicators, namely (1) national commitment includes a pledge of loyalty to Majapahit and the stipulation of the Kutara Manawa Dharmashastra law as the constitution of Demak. (2) Tolerance includes the equality of Nawa Dewata's Hinduistic cosmology with Walisongo's Sufistic cosmology and respect for the values of other religious beliefs. (3) Anti-violence includes expanding the influence of Islam through family ties with community leaders and nobles and applying da'wah based on religious humanism. (4) Accommodation of local culture includes Islamization of terms in Hindu-Buddhist and Kapitayan and harmonizing Islamic values with Hindu-Buddhist religious traditions, Kapitayan, and Bhairawa Tantra.